Identifying forest structure types using National Forest Inventory Data: the case of seáile oak forest in the Cantabrian range - Reque, J.A.
(En, Es)
ilus., 16 ref.
Keywords: QUERCUS PETRAEA; IDENTIFICACION; CARACTERISTICAS DEL RODAL; INVENTARIOS FORESTALES; SILVICULTURA; ESPAÑA; INVESTIGACION AGRARIA: SISTEMAS Y RECURSOS FORESTALES